2017
DOI: 10.1590/0104-1428.14216
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical properties of bio-based plasticizers mixtures on poly (vinyl chloride)

Abstract: ObstractThe use of mixtures of nontoxic and biodegradable plasticizers coming from natural resources is a good way to replace conventional phthalates plasticizers. In this study, two secondary plasticizers of epoxidized sunflower oil (ESO) and epoxidized sunflower oil methyl ester (ESOME) were synthesized and have been used with two commercially available biobased plasticizers; isosorbide diesters (ISB) and acetyl tributyl citrate (ATBC) in order to produce flexible PVC. Different mixtures of these plasticizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
(45 reference statements)
4
21
0
Order By: Relevance
“…Low volatility and different degrees of miscibility with polymers makes the plasticizers more flexible and durable products. The chemical structure of plasticizers is very diverse that belong to various classes of organic compounds including fluorinated substances, hydrocarbons, esters, ketones, alcohols, amines, fats, oligomers and others [5].…”
Section: Introductionmentioning
confidence: 99%
“…Low volatility and different degrees of miscibility with polymers makes the plasticizers more flexible and durable products. The chemical structure of plasticizers is very diverse that belong to various classes of organic compounds including fluorinated substances, hydrocarbons, esters, ketones, alcohols, amines, fats, oligomers and others [5].…”
Section: Introductionmentioning
confidence: 99%
“…The second thermal degradation stages have little difference, their temperature range was 410°C-570°C, corresponding to the C=C bond crosslinking. 21,22 Compared with blank PVC and PVC/B-SnO 2 , the AV P2 and ML 2 of the PVC/S-SnO 2 decreased by 5.6%, 5.6% and 7.5%, 0.58%, separately, where others barely changed. The thermal conductivity of PVC/S-SnO 2 was minimum; its value was 1.6% and 3.1% lower than that of blank PVC and PVC/ B-SnO 2 , respectively.…”
Section: Thermal Properties Of Pvc/sno 2 Compositesmentioning
confidence: 99%
“…Thus, for PVC, they have the additional characteristic of acting as a stabilizer. Recent studies have shown that epoxidized sunflower oil is also a good plasticizer and stabilizer for PVC, pure or combined with other plasticizers [7] . An additional advantage for the use of epoxidized oils as additives in polymers is that, they can act as stabilizers where the mechanism of degradation comprises evolution of acid substances, like HCl, the main by-product of the PVC degradation.…”
Section: Plasticizersmentioning
confidence: 99%